Mind Over Money: The Role of Investor Sentiment in Shaping ICO Fortunes - Tani, Joonas (My University, 2024)
Cryptocurrencies and Initial Coin Offerings are a relatively new phenomenon in the academic world. As their adoption progresses and matures, understanding the nature of this new technology and finance instruments becomes important. The cryptocurrency market is often driven by psychological factors and biases. This thesis examines the determinants of Initial Coin Offering fundraising success, with a focus on the role of investor sentiment in influencing fundraising outcomes. The existing literature on the relationship between investor attention and cryptocurrencies is scarce. Current academic research is strongly focused on the investor attention relationship between cryptocurrency returns. This thesis aims to provide academic evidence supporting the role of investor sentiment in fundraising. The research was conducted by analyzing the amount raised and whether ICO projects achieved their hard cap. Samples were collected from a cryptocurrency database consisting of 6416 ICO’s launched between 2018 and 2021. The final dataset used in this study was filtered into 404 samples, consisting of all desired variables. The theoretical framework was implemented by applying an Ordinary Least Squares (OLS) regression model, and the robustness of the results was further tested using binary regression models, Logit and Probit. The findings suggest that investor attention significantly influences the success of Initial Coin Offerings. The OLS regression reveals that an increase in the Google Trends Index is positively associated with the amount raised, and the odds of achieving the hard cap. Conversely, another proxy for investor sentiment, the Fear and Greed Index, finds only a minimal correlation with fundraising outcomes related to fearful emotions. Moreover, the results cannot confirm that a fearful environment affects ICO success.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance